(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article deals with the formation of historical city blocks, the development of principles for the use of architectural monuments in order to meet the needs of tourists. Durability of monuments, their correct and rational use. It is devoted to the problems of organizing, repairing and restoring protected areas in the historical part of the cities of Uzbekistan.